Power, Politics, and Education: Canadian Universities and International Education in an Era of New Geopolitics - Trilokekar, Roopa; El Masri, Amira; El Masry, Hani (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2020)
This paper focuses on the recent political spars between Canada and Saudi Arabia as well as China and their impact on Canadian universities. It asks three questions: (1) What key issues did Canada’s political strains with Saudi Arabia and China raise for Canadian universities’ international education (IE) initiatives and what issues were absent? (2) What do these key issues suggest about Canada’s approaches to IE in an era of new geopolitics? and (3) What implications can be drawn from these cases about Canadian university-government relations in the context of new geopolitics? Given the powerful role media plays in education policy, a systematic study was conducted across three main media sources to identify 74 articles and news releases between August 2018 and November 2019. Three dominant themes are identified and analyzed, each vividly illustrating the close ties between global politics, government foreign policy and IE within Canadian Universities. On the one hand, the narratives speak to concerns about IE as a risk to national security and, on the other, as a vehicle for Canada’s economic prosperity. However, what the media has not achieved is a broader discussion on how Canada needs to revisit its IE objectives and approaches in light of broader geopolitical shifts. Using the theoretical framework of soft power, the paper speaks to the limitations and short-sightedness of Canada’s approach to IE as soft power in this era of new geopolitics and concludes with three recommendations for Canada.